2023
DOI: 10.1111/faf.12782
|View full text |Cite
|
Sign up to set email alerts
|

Observing fish interactions with marine energy turbines using acoustic cameras

Abstract: Marine current energy converters such as tidal and riverine turbines have the potential to provide reliable, clean power. The risk of collision of fishes with marine energy turbines is not yet well understood, in part due to the challenges associated with observing fish at turbine sites. Turbidity and light availability can limit the effectiveness of optical sensors like video cameras, motivating the use of acoustic cameras for this task. However, challenges persist in collecting and interpreting data acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…If a marine animal were to enter the rotor swept area of a tidal turbine and collide with a blade, the consequences of such a collision could be a minor recoverable injury, immediate mortality, or a critical injury that results in permanent disability or death at a later time (i.e., latent mortality). There has never been an observation of a marine mammal struck by a turbine, and while there is video evidence of fish coming very close to a turbine [66], no harm has been observed. There are few studies that provide definitive information on what the consequences of a strike from a tidal turbine might be, although studies of equivalent forces on marine mammal tissue have shown that damage to skin, blubber, and muscle are likely recoverable from a typical tidal blade strike [39,119].…”
Section: Probability That Collision Results In Harm (Ie Critical Inju...mentioning
confidence: 99%
See 3 more Smart Citations
“…If a marine animal were to enter the rotor swept area of a tidal turbine and collide with a blade, the consequences of such a collision could be a minor recoverable injury, immediate mortality, or a critical injury that results in permanent disability or death at a later time (i.e., latent mortality). There has never been an observation of a marine mammal struck by a turbine, and while there is video evidence of fish coming very close to a turbine [66], no harm has been observed. There are few studies that provide definitive information on what the consequences of a strike from a tidal turbine might be, although studies of equivalent forces on marine mammal tissue have shown that damage to skin, blubber, and muscle are likely recoverable from a typical tidal blade strike [39,119].…”
Section: Probability That Collision Results In Harm (Ie Critical Inju...mentioning
confidence: 99%
“…Underwater passive acoustic monitoring systems can be deployed to detect and locate vocalizing marine mammals, while a range of active acoustic instruments like single-beam or split-beam echosounders, multibeam acoustic cameras and multibeam imaging sonars and acoustic cameras can all be used to assess the location of marine animals. Underwater video is often very useful in identifying species but collects large amounts of data for analysis and may be prone to failure [66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
The remote measurement of underwater targets is an important task for a range of disciplines, such as subsea engineering and maintenance (Cotter & Staines, 2023;Rofallski et al, 2020), defence operations (Reed et al, 2003), archaeology (Green et al, 2002) and marine science studies (Harvey et al, 2001;Harvey & Shortis, 1995). One of the most effective methods for measuring targets underwater is using stereo-video cameras
…”
mentioning
confidence: 99%